Child Maltreatment During the Pandemic. (February 2023) - Klika, J. Bart; Merrick, Melissa T.; Jones, Jennifer
What happened with child abuse and neglect during the pandemic? Emergency department and child welfare data suggest a decline in reports; however other sources of data suggest that risk for abuse and neglect remained high during COVID-19. In this commentary, the authors highlight the complicated, and at times contradictory, evidence as to what occurred with child abuse and neglect during the pandemic. The commentary concludes with suggestions for future research.